Non‐clinical safety assessment of single and repeated intramuscular administration of a human papillomavirus‐16/18 vaccine in rabbits and rats. Issue 12 (6th March 2015) - Segal, Lawrence; Morelle, Danielle; Kaaber, Kari; Destexhe, Eric; Garçon, Nathalie
Abstract The human papillomavirus (HPV)‐16/18 vaccine (Cervarix®) is a prophylactic vaccine for the prevention of cervical cancer. The vaccine contains recombinant virus‐like particles assembled from the L1 major capsid proteins of the cervical cancer‐causing viral types HPV‐16 and HPV‐18, and Adjuvant System 04 (AS04), which contains the immunostimulant MPL and aluminium salt. To evaluate potential local and systemic toxic effects of the HPV‐16/18 vaccine or AS04 alone, three repeated‐dose studies were performed in rabbits and rats. One rabbit study also included a single‐dose evaluation. In rabbits (~2.5 kg), the full human dose (HD) of the vaccine was evaluated (0.5 ml per injection site), and in rats (~250 g), 1/5 HD of vaccine was evaluated, corresponding to ≥ 12 times the dosage in humans relative to body weight. In both animal models, the treatment‐related changes included a slight transient increase in the number of circulating neutrophils as well as a local inflammatory reaction at the injection site. These treatment‐related changes were less pronounced after four doses of AS04 alone than after four doses of the HPV‐16/18 vaccine. Additional treatment‐related changes in the rat included lower albumin/globulin ratios and microscopic signs of inflammation in the popliteal lymph nodes. In both animal models, 13 weeks after the fourth dose, recovery was nearly complete, although at the injection site in some animals there were signs of discoloration, muscle‐fibre regeneration and focal points of macrophage infiltration. Therefore, in these non‐clinical models, the single and repeated dose administrations of the HPV‐16/18 vaccine or AS04 alone were safe and well tolerated. Copyright © 2015 John Wiley & Sons, Ltd.